Can a tDCS treatment enhance subjective and objective sleep among student-athletes?. Issue 4 (8th June 2021) - Charest, Jonathan; Marois, Alexandre; Bastien, Celyne H.
Abstract: Introduction: Previous studies have shown that student-athletes suffer from sleep difficulties. This study explored the impact of tDCS on sleep parameters among student-athletes. Method: Thirty student-athletes (15 females, 15 males, age 21.1 ± 2.1 years) were recruited. All participants underwent a series of questions to rule out depressive and anxiety disorders or any specific tDCS exclusion criteria. All participants were advised to maintain their usual sleep schedule. Results: Compared polysomnographic and Psychomotor Vigilance Task data analyses did not show any improvement after experimental tDCS. Regardless of groups, PVT mean reaction time was decreased. Regarding the questionnaires, data analyses showed improvement on the PSQI ( p < .001), ISI ( p < .001) and ASSQ ( p < .007) scores after tDCS. Discussion: tDCS appears to increase total sleep time and should be further explored. Improvements in subjective sleep suggest that tDCS bears interesting possibilities into the enhancement of sleep among student-athletes.